Natural and Engineered Sex Ratio Distortion in Insects - Compton, Austin; Tu, Zhijian (Frontiers in Ecology and Evolution, 2022)
Insects have evolved highly diverse genetic sex-determination mechanisms and a relatively balanced male to female sex ratio is generally expected. However, selection may shift the optimal sex ratio while meiotic drive and endosymbiont manipulation can result in sex ratio distortion (SRD). Recent advances in sex chromosome genomics and CRISPR/Cas9-mediated genome editing brought significant insights into the molecular regulators of sex determination in an increasing number of insects and provided new ways to engineer SRD. We review these advances and discuss both naturally occurring and engineered SRD in the context of the Anthropocene. We emphasize SRD-mediated biological control of insects to help improve One Health, sustain agriculture, and conserve endangered species